2002
DOI: 10.1067/mva.2002.122024
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid drainage reduces paraplegia after thoracoabdominal aortic aneurysm repair: Results of a randomized clinical trial

Abstract: Perioperative CSFD reduces the rate of paraplegia after repair of extent I and II TAAAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
363
1
9

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 645 publications
(379 citation statements)
references
References 32 publications
6
363
1
9
Order By: Relevance
“…However, TAAA open surgical or endovascular aneurysm repair (EVAR) is major extensive surgery and carries a significant risk of mortality and post-operative complications of which the most feared and devastating is that of paraplegia. This is a direct consequence of the restriction of spinal cord blood flow during surgical repair and consequently causes spinal cord ischaemia (SCI) [5]. Published rates of spinal cord ischaemia are varied worldwide can have been reported as high as 30% [6][7][8][9][10] .…”
mentioning
confidence: 99%
“…However, TAAA open surgical or endovascular aneurysm repair (EVAR) is major extensive surgery and carries a significant risk of mortality and post-operative complications of which the most feared and devastating is that of paraplegia. This is a direct consequence of the restriction of spinal cord blood flow during surgical repair and consequently causes spinal cord ischaemia (SCI) [5]. Published rates of spinal cord ischaemia are varied worldwide can have been reported as high as 30% [6][7][8][9][10] .…”
mentioning
confidence: 99%
“…Spinal catheter drainage as suggested by Hollier 9 , has now been shown to reduce the incidence of paraplegia in some large clinical series. 2,3 Reduction of intra-spinal pressure is intended to improve blood flow at any given perfusion pressure. Reimplantation of intercostal arteries is also an effort to maintain circulation to the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Reports from centers with a large experience with DT and TAA aneurysm repair have documented improved results when distal aortic perfusion and spinal catheter drainage are used. [1][2][3][4] These adjuncts attempt to address issues of organ dysfunction secondary to hypoperfusion. Additional maneuvers have been suggested which may help reduce the risk of postoperative complications.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebrospinal fluid drainage is often used as an adjunct for spinal cord protection following thoracoabdominal aortic aneurysm repair. Coselli et al 12 showed in a randomized control trial with and without CSF drainage following thoracoabdominal aortic aneurysm that 2.6% of patients developed neurologic deficits/ paraplegia with CSF drainage versus 13% of patients treated without CSF drainage.…”
Section: Treatment Options After An Intraoperative Scimentioning
confidence: 99%